IMPLEMENTASI DASHBOARD BUSINESS INTELLIGENCE UNTUK VISUALISASI DATA PINJAMAN DANA BERGULIR (STUDI KASUS : UPTD FASILITASI PEMBIAYAAN KOTA PAYAKUMBUH) - Fathu Rahmi; Dini Nurmalasari (ABEC Indonesia, 2021)
UPTD Payakumbuh City Financing Facilitation is a Micro Finance Institution that provides and manages assistance in the form of revolving fund loans to strengthen business capital for micro-entrepreneurs such as livestock, trade, agriculture and industry. Based on information obtained through interviews with the UPTD, there were difficulties in obtaining information related to micro-businesses and monitoring customer commitment. Where the data currently owned is still managed conventionally so that the UPTD is difficult to obtain information. Therefore, a system was Dashboard Business Intelligencecreated that could assist the UPTD in managing data and providing information related to micro-businesses to maximize loan funds so that loans can help improve the community's economy. This system is built using the Codeigniter Framework, the programming language PHP and MySQL as the DBMS. This system is tested using blackbox testing and user acceptance test (UAT). Based on the blackbox testing that has been done, the system functionality is in accordance with user expectations. Meanwhile, based on the user acceptance test (UAT) that has been carried out, it shows that 91% of the system that has been built has been accepted by the user and can help the UPTD in making decisions